(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
This essay brings elements of ongoing research for the Doctoral Thesis in Social Work at Universidade Estadual Paulista - UNESP Franca. Part of the author’s professional experience as a Social Worker in the implementation and monitoring of the Affirmative Action Policy in two Federal Institutions of Higher Education. The study aims to point out and reflect on the obstacles that students still face to enter and remain in Higher Education through Affirmative Actions at the moment that the policy completes ten years of implementation. Key-words: Affirmative Actions. College Education. Social Service.